2021
DOI: 10.1002/mar.21523
|View full text |Cite
|
Sign up to set email alerts
|

Neural resonance in consumers' right inferior frontal gyrus predicts attitudes toward advertising

Abstract: Advertising plays a critical role in the commercial success of services and products. However, despite a long history of attempts to evaluate the efficacy of advertisements, actual objective, consistent means of assessing and anticipating whether an advertisement might be effective and why it would be expected to translate to actual, desired purchasing decisions remain elusive—especially as this regards advertisements' ability to resonate or create emotional connections across audiences. In this study, focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Consistently with H3, only the ratings’ main effect was found in the LPP amplitudes. However, just as the deduction in the LPP Hypothesis section, the ERPs’ weakness in clarifying “one-to-one” causal relationships is long-lasting [ 76 ]. Thus, establishing whether one of these two explanations or their combination truly represents consumer psychological processes of experience product purchase is beyond the capacity of the current research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently with H3, only the ratings’ main effect was found in the LPP amplitudes. However, just as the deduction in the LPP Hypothesis section, the ERPs’ weakness in clarifying “one-to-one” causal relationships is long-lasting [ 76 ]. Thus, establishing whether one of these two explanations or their combination truly represents consumer psychological processes of experience product purchase is beyond the capacity of the current research.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in our study, one major drawback of ERPs is the interpretation of “one-to-one” causal relationships. Although the current techniques cannot directly clarify the two alternative explanations of LPP components, we hope that the current research successfully shows consumer neuroscience as a complementary link in theoretical systems assessing consumer behaviour from a holistic perspective, including behavioural, physiological, and neural aspects [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Liu et al (2018) and Cakir et al (2018) add to these findings by showing that using fNIRS/mfNIRS to measure neural brain activity is helpful in merchandising activity evaluation and examining the related decision-making processes. Just recently, He et al (2021) indicated further that mfNIRS is capable of exploring the neural correlates, which can predict attitudes towards advertisements, measuring brain regions of the right inferior frontal gyrus, which is ascribed to empathy and emotional contagion.…”
Section: Research-oriented Commonalitiesmentioning
confidence: 99%
“…The majority of the identified articles have focussed on validating fNIRS/mfNIRS in the field of consumer neuroscience (Kim et al , 2016; Krampe et al , 2018b; Liu et al , 2018; Cakir et al , 2018; Burns et al , 2018), followed by studies using fNIRS/mfNIRS to predict the future consumer behaviour (Shimokawa et al , 2009; Krampe et al , 2018a; Cha et al , 2019; Gier et al , 2020; He et al , 2021) and the exploration of cultural (Burns et al , 2018) and/or gender-specific differences (Nissen and Krampe, 2021; Duan et al , 2021). The scientific articles identified can, thus, be categorised according to four overarching themes in the use of fNIRS/mfNIRS: “validation” in marketing research, “behaviour prediction” based on neural cortical activity, exploration of “cultural differences” and evaluation of “gender differences”.…”
Section: Functional Near-infrared Spectroscopy/mobile Functional Near...mentioning
confidence: 99%
“…From the perspective of neuroscience, Lee (2016) adopted electroencephalogram (EEG) measurement to uncover the neural mechanism of consumer empathy in response to corporate social responsibility messages and found that high empathy individuals are more inclined to pay for prosocial brand products than low empathy ones. Recently, He et al (2021b) employed the functional near-infrared spectroscopy (fNIRS) technique to capture brain activations of subjects when they viewed advertising and demonstrated that empathic connections could increase positive attitudes of consumers toward advertising evaluation. However, in terms of brand extension evaluation, how individuals with varying levels of empathy respond to distant extensions under diverse brand associations, in particular, their neural mechanism, is unknown.…”
Section: Introductionmentioning
confidence: 99%